2016
DOI: 10.1002/14651858.cd010407.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bioidentical hormones for women with vasomotor symptoms

Abstract: BackgroundVarious hormone therapies (HT) are available to treat menopausal vasomotor symptoms. Bioidentical hormones are chemically identical to those produced by the human body, and several types are well-tested and available on prescription. Many women have opted for bioidentical hormone therapy (BHT) on the assumption that it is safer than other forms of HT. We evaluated the evidence. ObjectivesTo determine the effectiveness and safety of bioidentical hormones compared to placebo or non-bioidentical hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 99 publications
0
16
0
3
Order By: Relevance
“…revealed that estrone (E1) has low affinity for ERβ and ethinyl estradiol (EE) has higher affinity for ERα . In the same study, estriol (E3) was found not to antagonize the activity of estradiol (E2) as claimed by many proponents of b(HT) . Also, both bioidentical estradiol (bE2) and estriol (bE3) used in [b(HT)] were found to be full estrogen agonists .…”
Section: Determinants Of Bc Risk: Considerations For Bc Prevention Anmentioning
confidence: 90%
See 3 more Smart Citations
“…revealed that estrone (E1) has low affinity for ERβ and ethinyl estradiol (EE) has higher affinity for ERα . In the same study, estriol (E3) was found not to antagonize the activity of estradiol (E2) as claimed by many proponents of b(HT) . Also, both bioidentical estradiol (bE2) and estriol (bE3) used in [b(HT)] were found to be full estrogen agonists .…”
Section: Determinants Of Bc Risk: Considerations For Bc Prevention Anmentioning
confidence: 90%
“…The specific effects of estrogen and its metabolites on ER isoforms need to be carefully considered in developing combinatorial interventions with phytochemicals. Bioidentical hormone therapy [b(HT)] is being considered as an alternative to conventional hormone therapy (HT) . In a recent study, Perkins et al .…”
Section: Determinants Of Bc Risk: Considerations For Bc Prevention Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Custom‐compounded or bioidentical ovarian hormones appear superior to placebo in relieving moderate‐to‐severe hot flushes; however, their effectiveness relative to conventional MHT, the long term safety and the safety in patients with cancer have not been established 51 . Moreover, these drugs are not regulated by the Australian Therapeutic Goods Administration and their use cannot be recommended, particularly among cancer survivors.…”
Section: Management Optionsmentioning
confidence: 99%